Surface plasmon resonance and photoluminescence studies of Au and Ag micro-flowers - Zakaria, R.; Hamdan, K.S.; Noh, S.M.C.; Supangat, A.; Sookhakian, M. (Optical Society of America, 2015)
The surface plasmon resonance (SPR) and photoluminescence characteristics of gold and silver micro-flowers were compared to those of gold and silver nanoparticles. The microflower structures were grown under electron beam deposition using an alumina template. Both types of metallic micro-flowers showed systematic arrangements; they formed islands of flowers about 20 μm across, each one comprised of spikes ranging from 1 to 5 μm in length. A red shift in the SPR and enhancement intensity was observed for both micro-flowers and nanoparticles; the incremental increase was more than 50%. These results, which showed that gold and silver microflowers agglomerate at a micron size scale, are useful for the design of easier and more cost effective methods for large area fabrication, especially for particular plasmonic applications.